Penerapan Extreme Programming Untuk Pengembangan Sistem Pendokumentasian Akreditasi Program Studi Berbasis Web - Michail, Michail; Ratnasari, Anita (Jurnal Ilmiah Sains dan Teknologi, 2026)
This study aims to develop a web-based accreditation documentation system using the Extreme Programming (XP) method. The system was designed to address issues in manual document management, such as difficulties in tracking versions, data duplication, and slow validation processes. The development process was carried out gradually through direct discussions with users to ensure the system met their needs. The use of XP allowed iterative system development with continuous feedback. Testing was conducted using black-box testing with boundary value analysis, showing that all main features function properly, including document upload, validation, monitoring, and reporting. Compared to manual methods, this system offers better transparency, speeds up the process, and facilitates collaboration during accreditation. This system is expected to serve as a reference for other study programs facing similar problems.